Investigation the factors affecting customer’s post-purchase perceived risk in luxury products (case study: Apple Mobile Phone buyers) - Modaresi, Seyed Alireza; Asadollahi, Amin (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
In the present study, we examined the factors affecting customer’s post-purchase perceived risk in luxury products. The research method is applied in terms of purpose and it is descriptive in terms of survey type. The statistical population of this study is students of Islamic Azad University of Qazvin Branch using Apple mobile phones. In this study the sampling method is convenience sampling in which questionnaires are distributed among the sample. In the present study sample size is determined as variables and structural equation method is used for data analysis. The sample size is 384 persons. Questionnaire was used to collect data and structural equation technique was used for data analysis. The results also showed that financial, visual, hedonic and operational risks are the dimensions of perceived post-purchase risk in luxury goods.